BS48 Microrna editing is integral for interleukin-6 trans-signalling and leukocyte trafficking to ischemic tissues. (May 2019) - Gatsiou, Aikaterini; Tual-Chalot, Simon; Bonini, Francesca; Cesarini, Valeriana; Ortega-Gomez, Almudena; Shook, Kerida; Hoffmann, Jedrzej; Kwak, Shin; Selzman, Craig H.; Martini, Maurizio; Dimmeler, Stefanie; Gallo, Angela; et al.
Abstract : Background: /Aim: Adenosine to inosine RNA editing is an essential posttranscriptional RNA modification catalysed by adenosine deaminase acting on RNA -1 and -2 (ADAR1;ADAR2). Endothelial cells (ECs) attract and guide leukocytes to sites of ischemic tissue injury. Here we studied the role of RNA editing in ischemic disease. Methods: Primary human and murine vascular endothelial cell cultures were used to assess the EC responses to interleukin-6 (IL-6) or ischemia. For the animal studies, the effect of ADAR2 in acute and chronic ischemic disease was evaluated in cremaster muscle microcirculation by intravital microscopy, in peritoneal cavity after sterile peritonitis and in gastrocnemius muscle after hind-limb ischemia by 8-colour flow cytometry and immunohistochemistry (IHC) studies of Adar2-/-/tg as well as of i(nducible)EC-ADAR2 knockout (KO) mice. For the mechanistic studies, RNA sequencing, qRT-PCR, western blot, confocal microscopy target-specific miRNA editing studies, RNA-immunoprecipitation, microRNA/plasmid silencing/overexpression and luciferase reporter assays were used. For human studies, ischemic tissues derived from patients with acute or chronic ischemic heart disease were processed. Results: ADAR2, but not ADAR1, expression is induced by >2-fold in hypoxic ECs and in ischemic vascular endothelial cells in mice and humans. Unbiased gene ontology analysis of the whole EC transcriptome revealed that ADAR2 controls inflammatory responses and predominantly the expression of interleukin-6-signal transducer (IL6ST), the co-receptor of IL-6. Subsequently, ADAR2 controls IL-6 trans-signalling in ECs as documented by STAT3 phosphorylation and expression of the downstream leukocyte adhesion molecules, E-selectin and VCAM-1. IL-6-inflamed cremaster muscles showed that rolling and adhesion of leukocyte subsets to vascular wall were severely impaired in Adar2-/-/tg mice. Leukocyte transmigration was also diminished by >2-fold in Adar2-/-/tg and in iEC-ADAR2 KO mice in response to IL-6 or ischemia. Similar results were obtained for leukocyte rolling, adhesion and infiltration after acute (4h) and chronic (3d; 21d) ischemia from iEC-ADAR2 KO mice and human ischemic tissues. Next we studied how ADAR2 controls IL6ST expression. ADAR2-deficient EC miRNAome revealed the upregulation of a conserved group of miRNAs targeting the IL6ST mRNA including miR-199a-5p and miR-335-3p. In a single nucleotide level, ADAR2-induced RNA editing of the stem loops of the primary miR-199a1/2 and miR-335 directly disrupted Drosha recruitment to both and thus inhibited their maturation process. Accordingly, rescue experiments using miRNA-inhibitors restored IL6ST levels after ADAR2 deficiency. Conclusion: Taking together, inhibition of the microRNA maturation process by ADAR2-mediated RNA editing is integral for IL-6 trans-signalling in vascular endothelium and subsequent leukocyte trafficking to ischemic tissues in mice and humans. Conflict of interest: n/a